Partner or Former Partner Femicide’s Characterization and Discriminatory Hate Crimes - Pérez Manzano, Mercedes (2018)
This article aims to specify a coherent and useful interpretation of feminicide behavior (or as preferred by the author “femicide”), which is included, in a non -uniform manner- in several criminal definitions in Latin American legislations. Indeed, the author asserts the need for an individualized criminal protection of women against gender violence, and confirms the praiseworthy work it is being done in Latin America, yet femicide as a criminal offense in the region is not defined accurately. Thus, the author concludes this is the reflection of a criminal policy that suffers from inaccuracies, duplicities and, in some cases, excessive punitiveness. The author questions the criminal definition of femicide as the death of a “woman because of her condition as such” or other similar definitions that include the murder of a woman because of the mere fact of being a woman. When referring to the death of a woman committed by her partner or former partner, the author characterizes feminicide as a form of violence which constitutes an instrument of discriminatory domination, in other words, violence against women with the purpose of maintaining or re-establishing unequal power relationships or simply to reaffirm the discriminatory sense of his act, denying the victim his right to equality. From this perspective, the author discusses considering partner or former partner femicide as a hate crime, since the characteristic of this criminal definition is its collective dimension (the implicit threat to the collective) and the parallel fungible condition of the victim. In the opinion of the author, in partner or former-partner femicide the woman’s death is related to both the bias that exists towards women, how they should behaved (machismo), and what was expected of the victim (as herself). It is an individual phenomenon, of only one dimension. Under all these considerations the text culminates analyzing the Peruvian criminal type of femicide, acknowledging some successes but also reiterating their mistakes.